Haererehalobacter sp. JS1, a bioemulsifier producing halophilic bacterium isolated from Indian solar salt works. (18th May 2018) - Birdilla Selva Donio, Mariathason; Chelladurai Karthikeyan, Subbiahanadar; Michaelbabu, Mariavincent; Uma, Ganapathi; Raja Jeya Sekar, Ramaiyan; Citarasu, Thavasimuthu
Abstract : Bioemulsifier (BE)‐producing Haererehalobacter sp. JS1 was isolated and identified from the solar salt works in India. The BE was extracted, purified, and characterized by Gas Chromatography‐Mass Spectrometry (GC‐MS) analysis. Emulsification activity was performed against different oils and dye degradation potential against different dyes. The production of BE was optimized using different carbon sources (C), nitrogen sources (N), pH, and NaCl. BE screening methods revealed that, Haererehalobacter sp. JS1 was highly positive BE production. Identification by 16S rRNA sequencing and analyses was found that, the Haererehalobacter sp. JS1 was closely related to Salinicoccus halophilus and Haererehalobacter sp. The structural characterization analysis confirmed that the partially purified bioemulsifier belongs to siloxane‐type. Emulsification activity (E24) revealed that the bioemulsifier significantly ( p  < = 0.001) emulsified the commercial oils including coconut oil, gingelly oil, olive oil, and palmolein oils. Haererehalobacter sp. JS1 also significantly ( p  < = 0.001) degraded the dyes such as orange MR, direct violet, cotton red, reactive yellow, nitro green, and azo dye. RSM regression co‐efficient and contour plot analysis clearly indicated that the combination of pH and NaCl helped to increase BE production. Siloxane‐type of BE obtained from Haererehalobacter sp. JS1 was able to emulsify different oils and commercial dyes.